Strategi Pemberdayaan Masyarakat Oleh Lembaga Amil Zakat (Studi Kasus di IZI Bandar Lampung) - Sudiyo Sudiyo (Jurnal Publikasi Ilmu Manajemen, 2023)
Community empowerment programs are made by the government and non-governmental organizations as an effort to improve living standards and welfare. This research was conducted to find out the empowerment programs implemented by the Indonesian Zakat Initiative (IZI) as an amil zakat institution in the city of Bandar Lampung, how the implementation of the community empowerment program was implemented and felt by the people in need. his type of research is a qualitative research with a descriptive approach. Methods of data collection obtained by interviews, observation, and documentation. The results of the research reveal that based on the level of importance and priority programs set, the programs implemented include skills training programs and business assistance, patient assistance service programs in IZI to fit, scholarship programs for students in IZI to smart, and service programs disaster and ambulance in IZI to help. Empowering mentoring programs should be strengthened by maintaining a good approach that is soft skills in the form of spiritual strengthening, motivation and enthusiasm to rise, as well as mentoring and strengthening hard skills in the form of skills training and doing business. It will be more complete and comprehensive if the management is collaborated.